Al2O3 nanoparticles as surface modifier enables deposition of high quality perovskite films for ultra-flexible photovoltaics - Zhiyong Wang; Qingshun Dong; Ying Yan; Zikeng Fang; Guojun Mi; Mingzhu Pei; Shuhong Wang; Linghui Zhang; Jing Liu; Min Chen; Hongru Ma; Ruiting Wang; et al. (Advanced Powder Materials, 2024)
Advanced photovoltaics, such as ultra-flexible perovskite solar cells (UF-PSCs), which are known for their lightweight design and high power-to-mass ratio, have been a long-standing goal that we, as humans, have continuously pursued. Unlike normal PSCs fabricated on rigid substrates, producing high-efficiency UF-PSCs remains a challenge due to the difficulty in achieving full coverage and minimizing defects of metal halide perovskite (MHP) films. In this study, we utilized Al2O3 nanoparticles (NPs) as an inorganic surface modifier to enhance the wettability and reduce the roughness of poly-bis(4-phenyl) (2,4,6-trimethylphenyl) amine simultaneously. This approach proves essentials in fabricating UF-PSCs, enabling the deposition of uniform and dense MHP films with full coverage and fewer defects. We systematically investigated the effect of Al2O3 NPs on film formation, combining simulation with experiments. Our strategy not only significantly increases the power conversion efficiency (PCE) from 11.96% to 16.33%, but also promotes reproducibility by effectively addressing the short circuit issue commonly encountered in UF-PSCs. Additionally, our UF-PSCs demonstrates good mechanical stability, maintaining 98.6% and 79.0% of their initial PCEs after 10,000 bending cycles with radii of 1.0 and 0.5 ​mm, respectively.